Application of Cooperative Problem Posing and Prior Motivation Towards Students Learning Outcomes - Fauzan Sulman (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
The students’ physics learning achievement at UIN STS Jambi was still low. It was caused by teachinglearning process which was still dominated by lecturer (Lecterer Centered) and the students lack of priormotivation to learn Physics Statistic. One of the solutions to solve those problems was that applying thecooperative problem possing model. This research was aimed at investigating the interaction ofcooperative problem posing model and prior motivation towards students’ learning achievement ofphysic statistic. The Population of this research was 41 students and sample was 20 students. It wastaken by using total sampling technique. This research was conducted in two classes namely experimentand control class. In experiment class, the students were taught by using cooperative problem posingmodel while students in control class were taught by using conventional model. Every class had twoclassifications of students, high motivated students and low motivated students. The data were taken fromquestionnaire and test which were conducted before and after treatment. Furthermore, the data wereanalyzed by using t-test and two ways anova for different number of sample. The results of data analysisshowed that there was no interaction between cooperative problem posing model and prior motivationtowards students’ learning achievement in cognitive domain.